TRANSLATING TAYEB SALIH’S PSYCHOLOGICAL TRAUMA AS REPRESENTED IN HIS NOVEL SEASON OF MIGRATION TO THE NORTH: A SEARCH FOR BELONGINGNESS - ALHASAN, NAWAL ABUZWAID; UNISSA, RAEES (Innovare Journal of Social Sciences, 2024)
Tayeb Salih, a prominent British author of Arabic language and origin is regarded as a pioneer who carved an identity of African-Arab literature globally. Salih acclaimed in one of his interviews in the Arabic press that he attempted to reshape the East and West relationship conceived by the world. He stated that the West romanticizes the idea of the East-West interaction merely as an emotion whereas it is an unresolved conflict that leads a trauma related to loss of identity, belongingness, and existentialism (Salih, 1929). Denys Johnson-Davies, an accredited translator, credited with making Arabic literature accessible to readers of the English language, who also translated Salih’s Season of Migration to the North (1966) regards the author and this literary piece as an intelligent work on East-West conflict produced by any Western or non-Western author. Season of Migration to the North provides a tapestry of events, multi-layered interpretations, traumatic outbreaks, struggles to identify with the world and finally succumbing to the pain. It is not a simple story of physical migration and the life of an African on the European land. It is an embodiment of an emotional, spiritual, religious, and mental search for belongingness. This present research is an attempt to capture the journey of the protagonist Mustafa Saeed and his life from his birth as a slave in the then colony of Britain, Sudan to his migration to Britain as a free individual. The rollercoaster of events that shape him and his destiny. Did he manage to break the clutches of his birth and slavery? Did he attain freedom from his belongingness to a British colony? Did he get peace to fly away from his roots is what makes this novel an extremely viable research material. The authors attempt to explore the psychological trauma and translate the author’s search for belongingness and understand the East-West relationship from his perspective.